Capsule Endoscopy in Inflammatory Bowel Disease: A Systematic Review - Pal, Partha; Banerjee, Rupa; Gupta, Rajesh; Reddy, Palle Manohar; Reddy, D Nageshwar; Tandan, Manu (Journal of Digestive Endoscopy, 2023)
The role of video capsule endoscopy (VCE) in inflammatory bowel disease (IBD) has evolved from small bowel to a panenteric evaluation tool over the past two decades. We systematically reviewed the techniques, applications, outcomes, and complications of VCE in IBD. A systematic literature search was performed using PubMed, Embase, and Medline. All relevant original articles involving VCE in IBD were included from 2003 to July 2022. After screening 3,089 citations, finally 201 references were included. The diagnostic yield of VCE in suspected Crohn's disease (CD) was highly variable (6–80%) with excellent sensitivity (77–93%) and specificity (80–89%). The diagnostic yield in known CD was 52 to 88.3% leading to a change in management (26–75%) and disease reclassification with variable retention rates. VCE was superior to small bowel series, computed tomography (CT) and could be better than magnetic resonance enterography (MRE), especially for proximal and superficial lesions. Colon or panenteric VCE has strong correlation to ileo-colonoscopy (IC) and combined magnetic resonance imaging and IC, respectively. The VCE retention rate in CD is higher in known CD which significantly decreases after the negative patency capsule test or CT/MRE. VCE can identify lesions beyond the reach of IC in postoperative CD. Colon Capsule Endoscopy is a noninvasive monitoring tool in ulcerative colitis (UC) having a strong correlation with IC and may uncover small bowel involvement. VCE is specifically useful in IBD-unclassified (IBD-U) which can lead to the diagnosis of CD in 16.7 to 61.5%. Various scoring systems have been established and validated for small bowel CD (Lewis score and capsule endoscopy CD activity index—CECDAI), UC (capsule scoring of UC: Capsule Scoring of Ulcerative Colitis), panenteric evaluation (Capsule Endoscopy Crohn's Disease Activity Index, Elaikim score), and flare prediction (APEX score). Technological advances include double head, three-dimensional reconstruction, sampling system, panoramic view (344 and 360 degree lateral), and panenteric capsule. Artificial intelligence and software like TOP100 and Quickview can help reduce capsule reading time with excellent sensitivity and specificity. VCE in IBD has widespread application in suspected and known small bowel CD, monitoring of UC, postoperative CD, IBD-U, and for panenteric evaluation. Patency capsule testing helps to reduce retention rates significantly. Artificial intelligence and technical advances can help evolve this novel technology.
Keywords: video capsule endoscopy; Crohn's disease; ulcerative colitis; inflammatory bowel disease; patency capsule